Transport, magnetic and vibrational properties of chemically exfoliated few‐layer graphene. Issue 11 (21st July 2015) - Márkus, Bence G.; Simon, Ferenc; Chacón‐Torres, Julio C.; Reich, Stephanie; Szirmai, Péter; Náfrádi, Bálint; Forró, László; Pichler, Thomas; Vecera, Philipp; Hauke, Frank; Hirsch, Andreas
Abstract: Abstractauthoren We study the vibrational, magnetic and transport properties of Few Layer Graphene (FLG) using Raman and electron spin resonance spectroscopy and microwave conductivity measurements. FLG samples were produced using wet chemical exfoliation with different post‐processing, namely ultrasound treatment, shear mixing, and magnetic stirring. Raman spectroscopy shows a low intensity D mode which attests a high sample quality. The G mode is present at 1580 cm − 1 as expected for graphene. The 2D mode consists of 2 components with varying intensities among the different samples. This is assigned to the presence of single and few layer graphene in the samples. Electron Spin Resonance (ESR) spectroscopy shows a main line in all types of materials with a width of about 1 mT and a g ‐factor in the range of 2.005 − 2.010 . Paramagnetic defect centers with a uniaxial g ‐factor anisotropy are identified, which shows that these are related to the local sp 2 bonds of the material. All kinds of investigated FLGs have a temperature dependent resistance which is compatible with a small gap semiconductor. The difference in resistance is related to the different grain size of the samples.